EVIDENCE FOR TIDAL UPWELLING ACROSS THE SILL OF AMBON BAY - Wenno, L. F.; Anderson, James Jay (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1984)
Temperature observations across the sill of Ambon Bay in August 1982 and a model suggest that during the upwelling season of the south east monsoon tidal upwelling on the flood tide can suck thermocline water up the outer slope of the sill from a depth of 50 to 80 m. The water enters over the 10 m sill and replaces the bottom water in the inner part of Ambon Bay.